2023
DOI: 10.3389/fimmu.2023.1287130
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking and effect of released DNA on cGAS-STING signaling pathway and cardiovascular disease

Zimo Zhou,
Changhan Ou-yang,
Qingjie Chen
et al.

Abstract: Evidence from clinical research and animal studies indicates that inflammation is an important factor in the occurrence and development of cardiovascular disease (CVD). Emerging evidence shows that nucleic acids serve as crucial pathogen-associated molecular patterns (PAMPs) or non-infectious damage-associated molecular patterns (DAMPs), are released and then recognized by pattern recognition receptors (PRRs), which activates immunological signaling pathways for host defense. Mechanistically, the released nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 165 publications
0
2
0
Order By: Relevance
“…Though MTMR4 may affect aortic aneurysm via affecting TGFβ signaling pathway, there is no direct evidence that MTMR4 has definite curable effects on aortic aneurysm. In addition, Dy et al (2019) found that MTMR3/MTMR4 regulated interferon gene stimulating factor (STING) trafficking by regulating ptdins3p production, suggesting that MTMR3/MTMR4 may be a potential therapeutic target in the process of myocardial fibrosis, macrophage infiltration and cardiac inflammatory response in patients with diabetes and obesity mediated by STING signaling, which needs to be further experimentally verified ( 43 ).…”
Section: Roles Of Mtmrs In Cardiovascular Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Though MTMR4 may affect aortic aneurysm via affecting TGFβ signaling pathway, there is no direct evidence that MTMR4 has definite curable effects on aortic aneurysm. In addition, Dy et al (2019) found that MTMR3/MTMR4 regulated interferon gene stimulating factor (STING) trafficking by regulating ptdins3p production, suggesting that MTMR3/MTMR4 may be a potential therapeutic target in the process of myocardial fibrosis, macrophage infiltration and cardiac inflammatory response in patients with diabetes and obesity mediated by STING signaling, which needs to be further experimentally verified ( 43 ).…”
Section: Roles Of Mtmrs In Cardiovascular Systemmentioning
confidence: 99%
“…In spite of the effect on promoting late autophagy, MTMR6 also exerts as an antagonism under stress via interference with PI3K signal pathway and inhibiting formation of autophagosome ( 4 ). There have also been reports that deletion of either the MTMR6 or the MTMR8/MTMR9 complex leads to an increase in autophagy ( 43 , 91 ). Wang et al found that negative regulation of MTMR6 can inhibit the proliferation of ovarian cancer cells and promote apoptosis.…”
Section: Common Biological Functions Of Mtmrsmentioning
confidence: 99%